Separator and secondary battery
By designing the structure of the base film layer and the inorganic ceramic layer on the secondary battery separator, evenly distributing the bonding points, the problems of insufficient high-temperature cycling performance and purple spot lithium analysis are solved, and better bonding force and battery performance are achieved.
Patent Information
- Application Number
- CN202411272964.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-03
AI Technical Summary
The existing secondary batteries have shortcomings in high-temperature cycling performance, and the use of polyvinylidene fluoride coating will lead to poor adhesion and purple lithium spot lithium, affecting safety performance and service life.
Design a membrane with a surface composed of a base film layer and an inorganic ceramic layer, and the bonding points are evenly distributed in the bonding layer. The longest diameter of the bonding points is averaged 20μm to 500μm, and the number of bonding points in the area is 20~150. The distance between adjacent bonding points is between 20 μm and 600 μm, and the projection area accounts for 20 % to 64.5% of the area, so as to improve adhesion and uniformity, and reduce deformation and purple spot lithium debris.
It significantly improves the high-temperature cycling performance of secondary batteries, reduces the occurrence of purple lithium-ion excision, improves the adhesion between the separator and the electrode, extends the service life of the battery, and does not rely on polyvinylidene fluoride coating.
Smart Images

Figure CN119253197A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to a diaphragm and a secondary battery. Background Art
[0002] As a kind of energy storage equipment, secondary batteries are widely used in portable electronic products, electric vehicles, aerospace, energy storage and other fields. With the expansion of application fields, the energy density and charging rate of current secondary batteries are also increasing, but their high temperature cycle performance is still difficult to improve. Summary of the invention
[0003] The present application can provide a diaphragm and a secondary battery, wherein the surface adhesive force of the diaphragm of the present application is relatively strong and the adhesive force distribution is relatively uniform. When the diaphragm of the present application is used in a secondary battery, the high temperature cycle performance of the secondary battery can be improved.
[0004] In the first aspect, the present application provides a diaphragm, which includes a base film layer, the base film layer contains a bonding layer, the bonding layer is composed of a plurality of bonding points, in the bonding layer, the longest diameter of the bonding points is 20 μm to 500 μm on average, and there are 20 to 150 bonding points in any area on the surface of the bonding layer, and the length of the area is 3470 μm and the width is 2600 μm.
[0005] The inventors found that due to the high energy density of secondary batteries, the diaphragm is usually set wide and thin, but this will cause the diaphragm and the positive and negative electrodes on both sides of the diaphragm to be easily deformed, and the circulation interface of the secondary battery is also prone to purple lithium precipitation, resulting in reduced safety performance and service life of the secondary battery; in order to reduce the occurrence of this phenomenon, the current solution is usually to set a polyvinylidene fluoride coating in the diaphragm, but the polyvinylidene fluoride coating has poor adhesion, which will not only cause the diaphragm and the positive and negative electrodes to be easily deformed, but also deteriorate the high-temperature cycle performance of the secondary battery.
[0006] Based on the above technical scheme of the present application, the inventors have found that a bonding layer composed of bonding points is respectively arranged on the surface of the base film layer and the inorganic ceramic layer, and the bonding points in any area of 3470 μm long and 2600 μm wide in the bonding layer are controlled within the range of 20 to 150, and the longest diameter of the bonding points is set to an average of 20 μm to 500 μm, and the bonding force is provided by the bonding points on the surface of the diaphragm, so that the surface of the diaphragm not only has good bonding force, but also the distribution of bonding force is relatively uniform, which makes the diaphragm and the positive and negative electrodes bonded to the surface of the diaphragm bond tightly, without obvious bonding weak points, which can not only reduce the occurrence of purple spot lithium precipitation in the secondary battery, but also make it not easy to deform locally or as a whole. When the diaphragm of the present application is used in a secondary battery, the high temperature cycle performance of the secondary battery can be significantly improved. In addition, even if the secondary battery containing the diaphragm of the present application does not contain a polyvinylidene fluoride coating, the phenomenon of purple spot lithium precipitation is not easy to occur in the secondary battery.
[0007] In one embodiment of the present application, the separator satisfies at least one of the following conditions: (1) in the bonding layer, the distance between two adjacent bonding points is 20 μm to 600 μm; (2) the projected area of all bonding points in any region in the region accounts for 20% to 64.5% of the total area of the region; (3) there are 42 to 100 bonding points in any region; (4) the thickness of the bonding layer is D 1 , 0.2μm≤D 1 ≤4μm.
[0008] Based on the above embodiments, the separator that meets the requirements of the present application can be used in a secondary battery to further improve the high temperature cycle performance of the secondary battery.
[0009] In one embodiment of the present application, the separator satisfies at least one of the following conditions: (1) the longest diameter of the bonding point is 200 μm to 420 μm on average; (2) in the bonding layer, the distance between two adjacent bonding points is 150 μm to 380 μm; (3) the projected area of all bonding points in any region in the region accounts for 20% to 35% of the total area of the region; (4) 0.5 μm ≤ D 1 ≤2μm.
[0010] Based on the above embodiments, the separator that meets the requirements of the present application can be used in a secondary battery to further improve the high temperature cycle performance of the secondary battery.
[0011] In one embodiment of the present application, the projection shape of the bonding point in the region is at least one of a circle, a ring, an ellipse, a square or a rectangle.
[0012] Based on the above embodiments, the bonding performance of the separator and the cycle performance of the secondary battery can be further improved.
[0013] In one embodiment of the present application, the projected area of the ring shape is x, the area of the outer circle corresponding to the ring shape is y, and 10%≤x / y≤50%.
[0014] Based on the above embodiments, the dynamic performance of the secondary battery can be improved while ensuring adhesion.
[0015] In one embodiment of the present application, the adhesive layer includes a water-based polymer, and the polymerization monomers of the water-based polymer include at least two of butadiene, methyl acrylate, methyl methacrylate, styrene, butyl methacrylate, isooctyl acrylate, ethylene, propylene or vinylidene fluoride.
[0016] Based on the above implementation scheme, the water-based polymer itself has good bonding properties, and the main chain and side chain of the water-based polymer can be additionally grafted with a binder, which is beneficial to improving the bonding strength of the bonding layer.
[0017] In one embodiment of the present application, the inorganic ceramic layer comprises 85% to 95% inorganic particles and 5% to 15% binder by mass; the inorganic particles comprise at least one of aluminum oxide, silicon oxide, silicon dioxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zirconium oxide, zinc oxide, calcium oxide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate; and the binder comprises polyacrylate.
[0018] In one embodiment of the present application, a bonding layer is provided on one surface of the base film layer, an inorganic ceramic layer is provided on the other surface, and a bonding layer is provided on the surface of the inorganic ceramic layer away from the base film layer. Through the design of this special structure, the deformation of the positive and negative electrodes relative to the diaphragm can be effectively reduced, so that the diaphragm and the positive and negative electrodes bonded to the surface of the diaphragm are tightly bonded without obvious bonding weak points, which can not only reduce the occurrence of purple spot lithium precipitation in the secondary battery, but also improve the high temperature cycle performance of the battery.
[0019] In a second aspect, the present application provides a secondary battery, which includes an electrolyte and an electrode assembly, wherein the electrode assembly includes a positive electrode, the above-mentioned separator and a negative electrode in sequence along the thickness direction, and the positive electrode, the separator and the negative electrode are stacked. Therefore, the electronic device provided by the present application has good performance.
[0020] In one embodiment of the present application, at 80° C., the bonding force between the separator and the positive electrode is 2 N / m to 12 N / m; and / or, the bonding force between the separator and the negative electrode is 2 N / m to 12 N / m.
[0021] In one embodiment of the present application, the electrolyte satisfies at least one of the following conditions: (1) based on the total mass of the electrolyte, the electrolyte includes acetonitrile with a mass content of 35% to 80%; (2) based on the total mass of the electrolyte, the electrolyte includes 1,3-propane sultone with a mass content of 0.3% to 4.5%.
[0022] Based on the above embodiments, the low temperature performance of the secondary battery can be significantly improved.
[0023] In one embodiment of the present application, the ratio of the mass contents of acetonitrile and 1,3-propane sultone is 20-100 based on the total mass of the electrolyte.
[0024] Based on the above embodiments, the low temperature performance of the secondary battery can be further improved.
[0025] Beneficial effects of this application:
[0026] The present application provides a diaphragm and a secondary battery, wherein the diaphragm includes a base film layer, and the surface of the base film layer is provided with an inorganic ceramic layer and a bonding layer, and bonding points are evenly distributed in the bonding layer, and in each bonding layer, the longest diameter of the bonding points is 20 μm to 500 μm on average. By setting bonding points to form a bonding layer, and controlling the number and size of bonding points in the bonding layer, the surface of the diaphragm can have good bonding force, and the bonding force distribution is relatively uniform. When an inorganic ceramic layer is provided on one surface of the base film and a bonding layer is provided on the other surface, the positive and negative electrodes can be more effectively bonded uniformly. When the diaphragm of the present application is used in a secondary battery, the high temperature cycle performance of the secondary battery can be improved, and the phenomenon of purple spot lithium precipitation is not easy to occur in the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 This is the CCD image of the bonding layer in Examples 1-5 of the present application. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of embodiments of the present application, rather than all embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application. Those who do not specify specific conditions in the embodiments are carried out according to the conditions recommended by normal conditions or manufacturers. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be obtained by commercial purchase.
[0030] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0031] The inventors have discovered that in order to increase the energy density of secondary batteries to meet usage requirements, the diaphragms, positive and negative electrodes inside the secondary batteries are all designed to be wide and thin; however, this will cause the diaphragm to deform easily, and the circulation interface of the secondary battery will also be prone to purple spot lithium precipitation, resulting in reduced safety performance of the secondary battery. Although there is currently a solution to use PCS coating in the diaphragm, this will cause the battery cell of the secondary battery to deform easily and will also deteriorate the high-temperature cycle performance of the secondary battery. Based on this, the inventors have discovered that when the diaphragm in the present application is used in a secondary battery, it can not only improve the cycle performance of the secondary battery, but also make it less likely for purple spot lithium precipitation to occur in the secondary battery. The secondary battery and diaphragm of the present application are described below:
[0032] The secondary battery of the present application includes an electrolyte and an electrode assembly, wherein the electrode assembly includes a positive electrode, a separator and a negative electrode in sequence along the thickness direction, and the positive electrode, the negative electrode and the separator are stacked.
[0033] Diaphragm
[0034] The separator is used to isolate the positive electrode and the negative electrode to prevent them from directly contacting and causing a short circuit. The diaphragm of the present application includes a base film layer, on which a bonding layer and an inorganic ceramic layer are arranged, wherein the bonding layer is composed of a plurality of bonding points, in which the longest diameter of the bonding points in the bonding layer is on average 20 μm to 500 μm, specifically 20 μm, 50 μm, 100 μm, 150 μm, 200 μm, 240 μm, 320 μm, 360 μm, 400 μm, 450 μm, 500 μm or any two of the above values, preferably 200 to 400 μm, and there are 20 to 150 bonding points in any area on the surface of the bonding layer, specifically 20, 30, 40, 42, 55, 67, 86, 92, 100, 120, 150 or any two of the above values, preferably 42 to 100; the length of the area is 3470 μm and the width is 2600 μm. In the present application, the bonding points on the surface of the diaphragm make the surface of the diaphragm not only have good bonding force, but also the distribution of bonding force is relatively uniform. Therefore, the diaphragm of the present application is not easy to deform, and the positive and negative electrodes bonded to both sides of the diaphragm are not easy to deform. When the diaphragm of the present application is used in a secondary battery, it can not only reduce the occurrence of purple spot lithium precipitation phenomenon at the cycle interface of the secondary battery, but also improve the high temperature cycle performance of the secondary battery. In addition, the bonding layer of the present application can be set on the surface of the base film layer or on the surface of the inorganic ceramic layer; when the bonding layer is set on the surface of the base film layer, the inorganic ceramic layer and the bonding layer are respectively set on both sides of the base film layer, and the structure of the diaphragm is that the bonding layer, the base film layer, and the inorganic ceramic layer are stacked in sequence; when the bonding layer is set on the surface of the inorganic ceramic layer, the inorganic ceramic layer and the bonding layer are set on the same side of the base film layer, and the inorganic ceramic layer is in contact with the base film layer, and the structure of the diaphragm is that the bonding layer, the non-polar ceramic layer, and the base film layer are stacked in sequence. Of course, in some embodiments of the present application, in order to better improve the performance of the diaphragm, a bonding layer may be provided on one of the surfaces of the base membrane layer, an inorganic ceramic layer may be provided on the other surface, and a bonding layer may also be provided on the surface of the inorganic ceramic layer away from the base membrane layer. At this time, the structure of the diaphragm is a bonding layer, an inorganic ceramic layer, a base membrane layer, and a bonding layer stacked in sequence.
[0035] It should be noted that the present application has no special restrictions on the shape of the bonding point. Since the three-dimensional shape of the bonding point is not intuitive enough, the present application describes the shape of the bonding point in the region by the projection shape of the bonding point. Specifically, the projection shape of the bonding point in the region can be at least one of a circle, annular ring, ellipse, square or rectangle. When the projection shape of the bonding point in the region is annular ring, in some embodiments of the present application, the projection area of the annular ring is x, and the area of the outer circle corresponding to the annular ring is y, 10%≤x / y≤50%. It should also be noted that the "longest diameter of the bonding point" in the present application is also relative to the projection shape of the bonding point in the region, which refers to the distance between the two points farthest apart in the projection shape; specifically, when the projection shape of the bonding point is a circle, the "longest diameter" refers to the diameter of the circle; when the projection shape is annular ring, the "longest diameter" refers to the radius of the large circle of the annular ring; when the projection shape is an ellipse, the "longest diameter" refers to the length of the major axis of the ellipse; when the projection shape is a square or a rectangle, the "longest diameter" refers to the diagonal length of the square or rectangle.
[0036] In some embodiments of the present application, in order to further improve the dynamic performance of the diaphragm, in the bonding layer of the diaphragm, the distance between two adjacent bonding points is 20 μm to 600 μm, preferably 150 μm to 380 μm. In the present application, "the distance between two adjacent bonding points" refers to the distance between the projections of two adjacent bonding points, which is the distance between the closest parts of the two projections.
[0037] The present application does not have any special restrictions on the distribution of bonding points in the region. In the actual production process, based on the needs of the preparation process, the bonding points in the region are usually relatively uniform and regular, that is, the distance between two adjacent bonding points in the region is basically the same, and the projection of the bonding points in the region can form a pattern that is approximately rectangular or square; as an example, in this embodiment, the distribution of bonding points in the region is relatively uniform, and the projection of the bonding points can be arranged into a pattern that is approximately rectangular. In addition, in the specific embodiments of the present application, since there are more than one adjacent points to each bonding point, and the arrangement of the bonding points in the embodiments of the present application is relatively regular, the "distance between two adjacent bonding points" refers to the average distance, and the specific algorithm is: average distance = the sum of the distances between all two adjacent bonding points in the region / the number of bonding points in the region.
[0038] In some embodiments of the present application, in order to further enhance the surface adhesion of the diaphragm and make the diaphragm less susceptible to deformation, the projected area of all bonding points in any region of the adhesive layer in the region generally accounts for 20% to 64.5% of the total area of the region, preferably 20% to 35%.
[0039] The present application has no particular limitation on the thickness of the adhesive layer. In actual use, in order to further enhance the surface adhesive force of the diaphragm and make the diaphragm less prone to deformation, the thickness of the adhesive layer D 1 Usually between 0.2μm and 4μm, preferably 0.5μm≤D 1 When there are two adhesive layers, the thickness of the two adhesive layers may be the same or different, but in actual operation, in order to reduce the difficulty of the process of preparing the adhesive layers, the thickness of the two adhesive layers is usually the same.
[0040] In addition, the present application generally adopts a coating method to prepare the bonding layer in the diaphragm, and the coating equipment selects one of gravure, micro-gravure, screen printing, and extrusion coating. In order to more conveniently control the number, spacing, and size of bonding points, as an example, the bonding layer is prepared by screen printing coating in the specific embodiment of the present application. When using this method, the number, spacing, and size of bonding points in the bonding layer can be changed by replacing screen printing plates with different mesh sizes.
[0041] In some embodiments of the present application, the bonding layer includes a water-based polymer, and the polymerized monomers of the water-based polymer include at least two of butadiene, methyl acrylate, methyl methacrylate, styrene, butyl methacrylate, isooctyl acrylate, ethylene, propylene, or vinylidene fluoride. The water-based polymer has good bonding properties, and the main chain and side chain of the water-based polymer can be additionally grafted with a binder, which is beneficial to improving the bonding strength of the bonding layer. For example, acrylic acid, methyl methacrylate, butyl acrylate, octyl acrylate, isooctyl acrylate, butadiene, or acrylonitrile can be grafted onto the water-based polymer.
[0042] In addition, the present application has no particular restrictions on the material and thickness of the base film layer and the inorganic ceramic layer, as long as the purpose of the present application can be met. For example, the material of the base film layer can be at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be used. The inorganic ceramic layer may include 85% to 95% inorganic particles and 5% to 15% binder, wherein the inorganic particles include at least one of aluminum oxide, silicon dioxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zirconium oxide, zinc oxide, calcium oxide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate; the binder includes polyacrylate.
[0043] Since the secondary battery in the present application contains the above-mentioned separator, the secondary battery in the present application has good high-temperature cycle performance. Moreover, at 80°C, the bonding force between the separator and the positive electrode, and the bonding force between the separator and the negative electrode of the secondary battery in the present application can reach 2N / m to 12N / m.
[0044] Electrolyte
[0045] The electrolyte can transport lithium ions and electrons, ensuring the formation of a pathway inside the electrochemical device. Currently, there are also plans to reduce the purple spot lithium precipitation phenomenon in secondary batteries by changing the composition of the electrolyte, but this will lead to poor low-temperature performance of secondary batteries.
[0046] In some embodiments of the present application, in order to improve the low temperature performance of the secondary battery, the electrolyte satisfies at least one of the following conditions: (1) based on the total mass of the electrolyte, the electrolyte includes acetonitrile with a mass content of 35% to 80%; (2) based on the total mass of the electrolyte, the electrolyte includes 1,3-propane sultone with a mass content of 0.3% to 4.5%. Further, based on the total mass of the electrolyte, the mass content ratio of acetonitrile to 1,3-propane sultone can be in the range of 20 to 100, which can further improve the low temperature performance of the secondary battery.
[0047] positive electrode
[0048] The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. That is, in the present application, the positive electrode active material layer can be disposed on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. Moreover, in the present application, the "surface of the positive electrode current collector" can be the entire area of the positive electrode current collector, or it can be a partial area of the positive electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved.
[0049] The components of the positive electrode active material layer include a positive electrode active material, which can be any material that can reversibly embed and de-embed Li + 、Na + The positive electrode active material includes but is not limited to lithium iron phosphate (LiFePO 4 ), lithium cobalt oxide (LiCoO 2 ), at least one of lithium manganese oxide, lithium nickel oxide, ternary materials, etc., ternary materials include but are not limited to LiNi x Co y Mn z O 2 、LiNi x Co y Al z O2 At least one of the above, and the contents of Ni, Co, Mn, Al, etc. can be adjusted to ensure that x+y+z=1. For example, the ternary material can be LiNi 0.6 Co 0.2 Mn 0.2 O 2 、LiNi 0.88 Co 0.08 Mn 0.04 O 2 、LiNi 0.8 Co 0.15 Mn 0.05 O 2 、LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.88 Co 0.1 Mn 0.02 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiNi 0.88 Co 0.1 Al 0.02 O 2 wait.
[0050] In some embodiments of the present application, the components of the positive electrode active material layer also include a positive electrode conductive agent; the present application has no restrictions on the type of the positive electrode conductive agent, and any known conductive material can be used. Specifically, the positive electrode conductive agent includes, but is not limited to, at least one of acetylene black, Super-P and other carbon blacks, or amorphous carbon materials such as needle coke, or carbon nanotubes, or graphene, etc.
[0051] In some embodiments of the present application, the components of the positive electrode active material layer generally also contain a positive electrode binder. There is no particular limitation on the type of positive electrode binder used in the manufacture of the positive electrode active material layer. In the case of a coating method, any material that can be dissolved or dispersed in the liquid medium used in electrode manufacturing can be used. The positive electrode binder includes, but is not limited to, any one or at least two of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymers or their hydrides, ethylene-propylene-diene terpolymers (EPDM), styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers or their hydrides; soft resin polymers such as isotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; polymer compositions having ionic conductivity of alkali metal ions (especially lithium ions), etc.
[0052] In the positive electrode, the type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. The material of the positive electrode current collector includes, but is not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In addition, in order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode active material layer, a conductive additive or a conductive coating may be provided on the surface of the positive electrode current collector. Conductive additives include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. The conductive coating may be a mixture layer of an inorganic oxide, a conductive agent, and a positive electrode binder.
[0053] When preparing the positive electrode, the components in the positive electrode active material layer can be dissolved or dispersed in a liquid solvent to prepare a positive electrode slurry, and then the positive electrode slurry is coated on the positive electrode collector and dried to form a positive electrode active material layer on the positive electrode collector, thereby obtaining a positive electrode. When the positive electrode is prepared in this way, the solvent in the positive electrode slurry is not particularly limited, as long as it can dissolve or disperse the above components. Specifically, the solvent in the positive electrode slurry includes but is not limited to N-methylpyrrolidone (NMP), ethylene carbonate (EC), etc. In addition, when preparing the positive electrode, the components in the positive electrode active material layer can also be dry mixed to form a sheet, and then the obtained sheet is crimped to the positive electrode collector.
[0054] negative electrode
[0055] The negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the components of the negative electrode active material layer include negative electrode active substances. That is, in the present application, the negative electrode active material layer can be disposed on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. Moreover, in the present application, the "surface of the negative electrode current collector" can be the entire area of the negative electrode current collector, or it can be a partial area of the negative electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved.
[0056] The negative electrode active material layer generally contains negative electrode active materials, and the present application does not have any particular restrictions on the negative electrode active materials. Specifically, the negative electrode active material may include at least one of a carbon material or a silicon-based material. More specifically, the carbon material includes but is not limited to at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon or soft carbon; the silicon-based material includes but is not limited to at least one of silicon, silicon-oxygen composite materials or silicon-carbon composite materials.
[0057] In some embodiments of the present application, the negative electrode active material layer generally further contains a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent includes but is not limited to at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene.
[0058] In some embodiments of the present application, the negative electrode active material layer may also contain a negative electrode binder and a thickener. The present application has no particular restrictions on the types of the negative electrode binder and the thickener, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to at least one of polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber or acrylic (ester) styrene-butadiene rubber; the thickener in the negative electrode slurry may include but is not limited to at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose.
[0059] In the negative electrode, the material of the negative electrode current collector includes but is not limited to copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc., and there is no special limitation in this application. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide).
[0060] In addition, in the present application, there is no particular limitation on the thickness of the negative electrode current collector and the negative electrode active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 12 μm, and the thickness of the single-sided negative electrode active material layer is 30 μm to 160 μm.
[0061] In addition, similar to the preparation of the positive electrode, when preparing the negative electrode, it can be configured into a negative electrode slurry, and then the negative electrode slurry is coated on the negative electrode current collector and dried to form a negative electrode active material layer on the negative electrode current collector to obtain the negative electrode; or the components in the negative electrode active material layer can be dry mixed to form a sheet, and then the obtained sheet is pressed onto the negative electrode current collector to form a negative electrode active material layer to obtain the negative electrode. The solvent in the negative electrode slurry includes any one of an aqueous solvent and an organic solvent. The aqueous solvent includes but is not limited to a mixed solvent of alcohol and water or water. Organic solvents include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide. In addition, in some other embodiments, when using an aqueous solvent, the components of the negative electrode slurry will also include a thickener and styrene-butadiene rubber (SBR) emulsion to slurry the negative electrode slurry, thereby adjusting the viscosity of the negative electrode slurry. The types of thickeners in the positive electrode slurry include, but are not limited to, at least one of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and their salts.
[0062] The secondary battery of the present application can be used in electronic devices, and the purpose of the electrochemical device of the present application is not particularly limited, and it can be used in any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0063] Example
[0064] The following uses lithium-ion secondary batteries as an example to provide examples and comparative examples to more specifically describe the implementation of the electrochemical device of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application.
[0065] Test methods and equipment:
[0066] Detection of bonding point quantity:
[0067] At any position on the surface of the diaphragm, select an area with a length of 3470 μm and a width of 2600 μm, use a Keyence VHX5000 CCD (Charge-coupled Device) electron microscope, magnify it 100 times, and observe and record the image information of the area. Figure 1 2 is the CCD diagram of Example 1-5. It can be seen from the figure that the projection shape of the bonding point is a circular ring.
[0068] The bond points in a region are counted as follows:
[0069] For bonding points that are not fully displayed in the area, if the portion in the selected area is less than 50% of the entire bonding points, it will not be counted in the total number. If it is equal to or greater than 50%, it will be counted as one bonding point.
[0070] Adhesion test:
[0071] The national standard GB / T 2790-1995, that is, the 180° peel test standard is adopted to test the adhesion between the separator and the positive electrode or the negative electrode. The separator and the positive electrode or the negative electrode are cut into 54.2 mm × 72.5 mm samples, and the separator is compounded with the positive electrode or the negative electrode. A hot press is used for hot pressing. The hot pressing conditions are: temperature 85°C, pressure 1 MPa, and hot pressing time 85 s (seconds). The compounded samples are cut into 15 mm × 54.2 mm strips. At 80°C, the adhesion between the separator and the positive electrode or the negative electrode is tested according to the 180° peel test standard.
[0072] Low temperature performance test:
[0073] Step 1: In an environment of 25°C, the formed secondary battery is charged and discharged for the first time. During discharge, it is discharged at a constant current of 0.2C to 3V. After that, the discharged secondary battery is allowed to stand for 5 minutes. Then, it is charged at a constant current of 0.5C to 4.53V. After that, it is charged at a constant voltage to 0.02C and allowed to stand for 60 minutes.
[0074] Step 2: Discharge at 0.2C to 2.5V, record the discharge capacity at this time, which is the discharge capacity of the first cycle of the secondary battery at 25°C, and then let it stand for 5 minutes.
[0075] Step 3: Place the secondary battery in 10℃, 0℃, -10℃, and -20℃ environments for discharge, and discharge at a constant current of 0.2C to 2.5V, and record the final discharge capacity of the secondary battery under each temperature condition. Before each discharge, this step will be charged in a 25℃ environment, and when charging, first charge at a constant current of 0.5C to 4.53V, and then charge at a constant voltage to 0.02C.
[0076] Step 4: Select the final discharge capacity of the secondary battery at -20°C, and use the following expression to calculate the low-temperature capacity retention rate of the secondary battery at -20°C:
[0077] Low-temperature capacity retention rate=(final discharge capacity of the secondary battery at -20°C / discharge capacity of the secondary battery at the first cycle at 25°C)×100%.
[0078] The greater the low-temperature capacity retention rate, the better the low-temperature performance of the secondary battery.
[0079] High temperature cycle performance test:
[0080] Place the secondary battery in a 45℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Then discharge the secondary battery at a constant current of 0.2C to 3V, then let it rest for 5 minutes, and measure the initial discharge capacity C of the secondary battery. 0 .
[0081] Then, charge and discharge are performed, wherein one charge and one discharge is recorded as one cycle, and 800 cycles are performed. The discharge capacity C of the secondary battery after 800 cycles is measured. 1 The charging process is as follows: (1) 3.5C constant current charging to 4.35V; (2) 3C constant current charging to 4.35V, constant voltage charging to 1.8C; (3) 1.8C constant current charging to 4.4V, constant voltage charging to 1.5C; (4) 1.5C constant current charging to 4.53V, constant voltage charging to 1.2C; (5) 1.2C constant current charging to 4.58V, constant voltage charging to 2100mA; (6) sleep for 5 minutes; (7) 0.5C constant current charging to 4.53V, constant voltage charging to 0.05C. The discharge process is as follows: 0.7C constant current discharge to 3.0V.
[0082] Capacity retention after 800 cycles at 45°C = C 1 / C 0 ×100%.
[0083] The higher the capacity retention rate, the better the high temperature cycle performance of the secondary battery.
[0084] <Preparation of Separator>
[0085] Inorganic boehmite particles with a Dv50 of 1 μm and polyacrylate are mixed in a mass ratio of 90:10 and dissolved in deionized water to form an inorganic coating slurry with a solid content of 50%. The obtained inorganic coating slurry is then evenly coated on one side of a base film layer made of polyethylene (PE) using a micro-concave coating method, and dried in an oven to obtain an inorganic ceramic layer.
[0086] 90g of polymer particles (weight average molecular weight of 600,000, polymerized monomers are butadiene and methyl acrylate in a molar ratio of 1:1) are added to a stirrer, and then 10g of sodium carboxymethyl cellulose is added, stirred and mixed evenly, 5g of wetting agent dimethylsiloxane is added, and then deionized water is added for stirring, and the viscosity of the slurry is adjusted to 2000mPa·s~5000mPa·s, and the solid content is 5%, to obtain a bonding layer slurry. Subsequently, the above bonding layer slurry is evenly coated on the surface of the inorganic ceramic layer and the base film layer by screen printing coating method, and the coating weight is 0.5g / m 2 , and then dried in an oven to form a bonding layer with a thickness of 1.7 μm.
[0087] <Preparation of negative electrode>
[0088] The negative electrode active materials artificial graphite, acetylene black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 96:1:1.5:1.5, and then deionized water is added as a solvent to prepare a negative electrode slurry with a solid content of 70%, and then a vacuum mixer is used to stir evenly. The negative electrode slurry is evenly coated on one surface of a copper foil with a thickness of 8 μm, dried at 110°C, and cold pressed to obtain a negative electrode sheet coated with a 150 μm negative electrode active material layer on one side, and then the above coating steps are repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. The negative electrode sheet is cut into a specification of 74 mm × 867 mm and welded to the pole ear for standby use.
[0089] <Preparation of positive electrode>
[0090] The positive electrode active materials lithium cobalt oxide, acetylene black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 94:3:3, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 75%, and then a vacuum mixer is used to stir evenly. The positive electrode slurry is evenly coated on one surface of an aluminum foil with a thickness of 12μm, dried at 90°C, and cold pressed to obtain a positive electrode sheet coated with a 100μm thick positive electrode active material layer on one side, and then the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. The positive electrode sheet is cut into a specification of 74mm×867mm and welded to the pole ear for standby use.
[0091] <Preparation of Electrolyte>
[0092] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents of ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) were mixed in a mass ratio of 20:30:20:28:2, and then lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent. 6 ) are dissolved and mixed uniformly to obtain an electrolyte. Based on the total mass of the electrolyte, LiPF 6 The mass content is 8%.
[0093] <Preparation of Secondary Battery>
[0094] The positive electrode, separator and negative electrode prepared above are stacked in order, so that the separator is between the positive electrode and the negative electrode to play a role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the moisture is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, shaping and other processes, a secondary battery is obtained.
[0095] Example 1-2 to Example 1-8
[0096] Except for adjusting the number of bonding points and the distance between adjacent bonding points according to Table 1, the rest is basically the same as Example 1-1.
[0097] Example 1-9 to Example 1-18
[0098] Except for adjusting the number of bonding points, the longest diameter and the distance between adjacent bonding points according to Table 1, the rest is basically the same as Examples 1-3.
[0099] Example 1-19 to Example 1-32
[0100] Except that the electrolyte is prepared in the following manner and the longest diameter of the bonding point is adjusted according to Table 1, the rest is basically the same as Example 1-4.
[0101] <Preparation of Electrolyte>
[0102] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents EC, DEC, PC, PP, and VC were mixed in a mass ratio of 20:30:20:28:2 to form a base solvent, and then LiPF was added to the base solvent. 6 , acetonitrile and 1,3-propane sultone, and mixed evenly to obtain an electrolyte. Based on the total mass of the electrolyte, LiPF 6 The mass content is 8%, the contents of acetonitrile and 1,3-propane sultone are shown in Table 1, and the remainder is the basic solvent.
[0103] Example 1-33 to Example 1-42
[0104] Except for adjusting the number of bonding points and the distance between adjacent bonding points according to Table 1, the rest is basically the same as Examples 1-4.
[0105] Comparative Examples 1 to 4
[0106] Except for adjusting the number of bonding points, the distance between adjacent bonding points or the longest diameter according to Table 1, the rest is basically the same as Example 1-1.
[0107] Table 1
[0108]
[0109]
[0110]
[0111] Note: x / y is the percentage of the projection area of the ring to the area of the outer circle corresponding to the ring in the projection shape of the bonding point; this is true for both Table 2 and Table 3.
[0112] Example 2-1 to Example 2-10
[0113] Except for adjusting the longest diameter of the bonding point and the thickness of the bonding layer according to Table 2, the rest is basically the same as Examples 1-5.
[0114] Table 2
[0115]
[0116]
[0117] Example 3-1 to Example 3-3
[0118] Except for adjusting the thickness of the adhesive layer and the type of the aqueous polymer in the adhesive layer according to Table 3, the rest is basically the same as Example 2-1.
[0119] Table 3
[0120]
[0121] As shown in Tables 1 to 3, it can be seen from the examples and comparative examples that the separator of the present application has strong bonding force and is evenly distributed. When used in a secondary battery, it can significantly improve the high temperature cycle performance of the secondary battery.
[0122] Particularly, when the thickness of the adhesive layer is in the range of 0.5 μm to 2 μm, the high temperature cycle performance of the secondary battery can be further improved.
[0123] In particular, when the electrolyte of the secondary battery contains 35% to 80% acetonitrile and / or 0.3% to 4.5% 1,3-propane sultone, the low-temperature performance of the secondary battery can be improved; and when the mass content ratio of acetonitrile to 1,3-propane sultone is 20 to 100, the low-temperature performance of the secondary battery can be further enhanced.
[0124] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements that are inherent to such process, method or article.
[0125] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0126] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.
Claims
1. A diaphragm, characterized in that: It includes a base film layer, which contains a bonding layer and an inorganic ceramic layer. The bonding layer is composed of multiple bonding points. In the bonding layer, the longest diameter of the bonding points is 20μm to 500μm on average. There are 20 to 150 bonding points in any area on the surface of the bonding layer. The length of the area is 3470μm and the width is 2600μm.
2. The diaphragm according to claim 1, characterized in that It meets at least one of the following conditions: (1) In the bonding layer, the distance between two adjacent bonding points is 20 μm to 600 μm; (2) The projected area of all the bonding points in any one of the regions in the region accounts for 20% to 64.5% of the total area of the region; (3) There are 42 to 100 bonding points in any one of the regions; (4) The thickness of the adhesive layer is D1, 0.2 μm≤D1≤4 μm.
3. The diaphragm according to claim 2, characterized in that It meets at least one of the following conditions: (1) The longest diameter of the bonding point is 200 μm to 420 μm on average; (2) In the bonding layer, the distance between two adjacent bonding points is 150 μm to 380 μm; (3) The projected area of all the bonding points in any one of the regions in the region accounts for 20% to 35% of the total area of the region; (4)0.5μm≤D1≤2μm.
4. The diaphragm according to claim 1, characterized in that A bonding layer is disposed on one surface of the base film layer, and an inorganic ceramic layer is disposed on the other surface. The bonding layer is disposed on a surface of the inorganic ceramic layer away from the base film layer.
5. The diaphragm according to claim 1, characterized in that The projection shape of the bonding point in the area is at least one of a circle, a ring, an ellipse, a square or a rectangle.
6. The diaphragm according to claim 5, characterized in that The projection area of the circular ring is x, the area of the outer circle corresponding to the circular ring is y, and 10%≤x / y≤50%.
7. The diaphragm according to any one of claims 1 to 6, characterized in that: The adhesive layer includes a water-based polymer, and the polymerization monomers of the water-based polymer include at least two of butadiene, methyl acrylate, methyl methacrylate, styrene, butyl methacrylate, isooctyl acrylate, ethylene, propylene or vinylidene fluoride.
8. The diaphragm according to claim 1, characterized in that The inorganic ceramic layer comprises 85% to 95% of inorganic particles and 5% to 15% of a binder by mass fraction; The inorganic particles include at least one of aluminum oxide, silicon dioxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zirconium oxide, zinc oxide, calcium oxide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate; and the binder includes polyacrylate.
9. A secondary battery, characterized in that: It comprises an electrolyte and an electrode assembly, wherein the electrode assembly comprises a positive electrode, a separator according to any one of claims 1 to 8 and a negative electrode in sequence along the thickness direction, and the positive electrode, the separator and the negative electrode are stacked.
10. The secondary battery according to claim 9, characterized in that: At 80° C., the bonding force between the separator and the positive electrode is 2 N / m to 12 N / m; and / or, The bonding force between the separator and the negative electrode is 2 N / m to 12 N / m.
11. The secondary battery according to claim 9, characterized in that: The electrolyte satisfies at least one of the following conditions: (1) Based on the total mass of the electrolyte, the electrolyte comprises acetonitrile in an amount of 35% to 80% by mass; (2) The electrolyte includes 1,3-propane sultone in an amount of 0.3% to 4.5% by mass based on the total mass of the electrolyte.
12. The secondary battery according to claim 11, characterized in that: The electrolyte includes acetonitrile and 1,3-propane sultone, and the mass content ratio of the acetonitrile to the 1,3-propane sultone is 20-100 based on the total mass of the electrolyte.
Citation Information
Patent Citations
Separator and lithium ion battery
CN107834007A
Non-uniform strip-shaped point coating as well as preparation method and application thereof
CN113258212A
Cited By
Diaphragm and preparation method and application thereof
CN120728168A
Separator and secondary battery
WO2026056935A1
Separator and secondary battery
WO2026056973A1